Effect of Gold Nanoparticles and Hydroxypropylmethylcellulose on the Activity of Two Novel Designed Antimicrobial Peptides: Effect of formulation components on the Antimicrobial Activity of AMP - Fathi, Fariba; Mahboubi, Arash; Noroozi Heris , Niloofar; Tabarzad, Maryam (Iranian Journal of Pharmaceutical Sciences, 2022)
Infectious wounds are one of the issues that significantly burden population lives and finances each year. Even though there have been significant breakthroughs in wound healing dressing, wound infections continue to be an issue. One of the latest techniques is using contemporary dressings containing antimicrobial agents to expedite wound healing and prevent infection. In the present study, the effect of gold nanoparticles (AuNPs) and hydroxypropylmethylcellulose (HPMC) as the main expedient of a hydrogel formulation on the bioactivity of two newly designed antimicrobial peptide (AMPs) was investigated. AuNPs were produced using two methods of chemical and biological synthesis. AuNPs were characterized individually and in the presence of AMPs in a stepwise manner. The antibacterial activity of these combinations against Staphylococcus aureus and Acinetobacter baumanii was evaluated. The results demonstrated that the stability of green-synthesized AuNPs was significantly superior to that of chemically synthesized AuNPs in presence of AMPs. In addition, the antibacterial activity of AMPs changed when combined with AuNPs and HPMC compared to its free state. This alteration was different based on the AMP identity and the combination composition. In the case of AMP1, designed based on regenerating islet-derived protein 3-alpha (REG3A), addition of AuNPs could enhance the antimicrobial activity. However, in the presence of another AMP (designed based on Cathelicidin-2), activity variations did not adopt with a distinct pattern. In general, the best antimicrobial activity was observed on the A. baumanii when a combination of green synthesized AuNPs, AMP derived from Cathelicidin-2 and HPMC was applied. In conclusion, since the inclusion of hydrogel and nanoparticles in the most combination conditions resulted in the efficacy reduction of AMPs, further efforts in selecting a suitable polymeric component should be made to develop an effective and inexpensive wound dressing formulation for this designed AMP.